The Factors That Affecting Students Learning Difficulties In The Islamic Eduction Subject - Akrim Akrim (Intiqad: Jurnal Agama dan Pendidikan Islam, 2020)
This study aims to determine the dominant factors that cause learning difficulties of students in participating in the Islamic Education (PAI) program at students of grade XI and XII at Laksamana Martadinata High School, Medan, North Sumatra. The research method used is descriptive research. This research was conducted in January to February 2020. 236 students of class XI and XII of Laksamana Martadinata Senior High School in Medan, North Sumatra were sampled in this study. Data collection techniques used in this study were by giving a questionnaire to the factors of student learning difficulties in following the Islamic Education subjects. The results showed that the internal factors causing the highest learning difficulties were health indicators with 70.68% and the external factors causing the highest learning difficulties were family indicators with 55.01%.